Synthesis, spectroscopic characterization and thermogravimetric analysis of two series of substituted (metallo)tetraphenylporphyrins - Al-Shewiki, Rasha K (Beilstein J Nanotechnol, 2017)
Subsequent treatment of H(2)TPP(CO(2)H)(4) (tetra(p-carboxylic acid phenyl)porphyrin, 1) with an excess of oxalyl chloride and HNR(2) afforded H(2)TPP(C(O)NR(2))(4) (R = Me, 2; iPr, 3) with yields exceeding 80%. The porphyrins 2 and 3 could be converted to the corresponding metalloporphyrins MTPP(C(O)NR(2))(4) (R = Me/iPr for M = Zn (2a, 3a); Cu (2b, 3b); Ni (2c, 3c); Co (2d, 3d)) by the addition of 3 equiv of anhydrous MCl(2) (M = Zn, Cu, Ni, Co) to dimethylformamide solutions of 2 and 3 at elevated temperatures. Metalloporphyrins 2a–d and 3a–d were obtained in yields exceeding 60% and have been, as well as 2 and 3, characterized by elemental analysis, electrospray ionization mass spectrometry (ESIMS) and IR and UV–vis spectroscopy. Porphyrins 2, 2a–d and 3, 3a–d are not suitable for organic molecular beam deposition (OMBD), which is attributed to their comparatively low thermal stability as determined by thermogravimetric analysis (TG) of selected representatives.